Viral coinfections among African children infected with human immunodeficiency virus type 1. - Chakraborty, R; Rees, G; Bourboulia, D; Cross, A; Dixon, JR; D'Agostino, A; Musoke, R; Boshoff, C; Rowland-Jones, S; Klenerman, P (2003)
City-dwelling children from Kenya who were infected with human immunodeficiency virus type 1 (HIV-1) were tested for coinfection with cytomegalovirus (CMV), human T cell lymphotropic viruses 1 and 2, Kaposi sarcoma-associated herpesvirus (KSHV), or hepatitis B, C, and G viruses. All children were found to be coinfected with CMV, whereas 5% had hepatitis G virus coinfection and 15% had KSHV coinfection. A protective role for hepatitis G virus cannot be excluded but likely affects only a minority of HIV-1-infected African children.